Power minimization in cooperative MIMO-OFDM systems with user fairness constraints - Chih-yu Hsu; Phee Lep Yeoh; Krongold, Brian S. (IEEE Wireless Communications and Networking Conference : [proceedings] : WCNC, 2015)
We propose a new resource allocation algorithm to support user fairness for downlink coordinated multipoint (CoMP) transmission with joint processing in multiuser multiple-input multiple-output (MIMO) orthogonal frequency-division multiplexing (OFDM) systems. The proposed algorithm utilizes successive convex approximation (SCA) to dynamically allocate the transmit powers between multiple CoMP base stations transmitting to multiple co-channel user terminals (UTs). The aim is to minimize the total transmit power subject to per-antenna power and per-UT rate constraints. Simulation results compare our SCA-based algorithm with iterative waterfilling.